Ironic Attitude of Main Actors of Political Stage - Sudra, Ewelina (Emocje i polityka. Sceny z życia polskiego parlamentu, 2016)
The aim of the article is an analysis of parliamentary speeches, both the verbal and non-verbal terms of the occurrence of an ironic attitude among the leading political actors. Visual analysis was extremely helpful in order to investigate actions, interactions, interpretative and communication processes, drawing the benefits from the achievements of interpretative and interactionist sociology. Visual analysis was used to describe and interpret emotional reactions of the political scene’s leading figures due to the applied irony. For this purpose, the following roles played by politicians in the parliamentary hall were highlighted: ironists, victims of irony and irony observers.